Avaliação da aprendizagem, formação docente e atuação profissional: uma análise desse processo na perspectiva de professores da educação básica - Natal, Isabella (Universidade Federal de São Carlos, 2022)
This study has as perspective the promotion of data that contribute to the improvement of the evaluation practices, as well as to a review in the approaches of the evaluation theme in the teacher education courses. Our goal is to analyze the understanding of teachers about the assessment of learning approached in the process of initial training and the consequences of the discipline of Educational Assessment in their professional performance. In this sense, the research contemplates as specific objectives the necessity to: investigate what teachers understand by evaluation, what they defend and what they propose; identify the evaluation practices mentioned by teachers in the teaching-learning process; punctuate the limits and the reaches of the evaluation practices pointed out by teachers in their professional performance. The research is based on the epistemology of practice as a theoretical strand and on authors such as: Tardif (2000, 2012), Nóvoa (1992, 2017, 2019) and Gauthier et al (1998), to discuss the knowledge that underlies both the training and the professional performance of teachers; in addition to Freitas (1995, 2009), Hoffmann (1995, 2005, 2008), Luckesi (1995, 2000 e 2011), Vasconcellos (2006) and Villas Boas (2011), who deal with learning evaluation and its implications in Basic Education. Based on a qualitative approach, Bogdan and Biklen (1994), Lüdke and André (1986) and Gil (2008), and an exploratory-descriptive study (SELLTIZ et al, 1965), the analysis was developed with the completion of questionnaires applied to teachers mostly working in the public education system, graduates of the undergraduate courses of a higher education institution, an Autarchy under private law in the city of Avaré, São Paulo, who attended the subject Educational Assessment, offered by the institution. The analyzed data were organized into four category of analysis: 1) identity profile of professional training; 2) evaluation of learning, curriculum and initial training; 3) evaluation of learning and professional knowledge; 4) evaluation of learning and pedagogical practices. The results point to a probable contribution of the discipline of Educational Assessment in the initial training and possible reflexes on the professional performance, promoting the appropriation of concepts incorporated into the teachers' speeches, from a diagnostic, formative and procedural perspective, collaborating with the diversity of processes and allowing a more reflective and investigative posture focused on student learning.
Learning assessment, teacher training, and professional performance: an analysis of this process from the perspective of basic education teachers.
Keywords: Avaliação da aprendizagem; Formação inicial; Atuação profissional; Learning assessment; Initial training; Professional performance; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL